2007
DOI: 10.2202/0027-6014.1832
|View full text |Cite
|
Sign up to set email alerts
|

Students' Technology Use and Its Effects on Peer Relationships, Academic Involvement, and Healthy Lifestyles

Abstract: The purpose of this study was to explore students’ technology use and its relationship with their psychosocial development. Previous research explored students’ computer use in conjunction with their cognitive development. This study examined the effects of computer use and other technologies, such as instant messaging, handheld gaming devices, and MP3 players, and the impact they have on students’ peer relationships, academic involvement, and healthy lifestyles. Results show both positive and negative effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…It was found that the implementation of ICT applications in education influence students in their pattern of engagement and their communication behaviors (Arend, 2004). Students using ICT for academic purposes are usually more involved in their educational endeavor, such as class participation and assignment completion (Lloyd et al, 2007). Another important concept arising from using e‐textbooks is the enhancement of students’ interaction with each other.…”
Section: Research Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the implementation of ICT applications in education influence students in their pattern of engagement and their communication behaviors (Arend, 2004). Students using ICT for academic purposes are usually more involved in their educational endeavor, such as class participation and assignment completion (Lloyd et al, 2007). Another important concept arising from using e‐textbooks is the enhancement of students’ interaction with each other.…”
Section: Research Modelmentioning
confidence: 99%
“…Doing so will allow them to digest e-textbook materials and understand the subjects. Defined as the quantity and quality of the physical and psychological energy that students dispense in academic activities, student involvement plays a critical role in improving learning experiences and performance (Astin, 1999; Student Involvement H1 H2 H3 Lloyd, Dean, & Cooper, 2007). According to the Student Development Theory (Astin, 1999), the more a student involves in academic activities, the greater will be the amount of student learning and personal development.…”
Section: Research Modelmentioning
confidence: 99%
“…If no other purposes are met, the Facebook groups may still be seen as successful for institutions which desire the fulfilment of these objectives. Regardless, there are a plethora of social media and pre-college topics to be examined further (Lloyd, Dean, and Cooper 2009). In particular, newer forms of social media targeting a younger crowd, such as YikYak, Instagram and Snapchat, should be examined for college-going patterns.…”
Section: Recommendations For Further Researchmentioning
confidence: 99%
“…The reason for this inability to think abstractly oddly enough is the very technology scholars argue make for exceptional students (for one example, see Huppert, Lomask, and Lazarowitz 2002; Lloyd, Dean, and Cooper 2009). 9 Computer technology is amazing, offering students images and text, but in the end, it remains a visual medium.…”
Section: Changing the Program To Break The Web Paradigmmentioning
confidence: 99%